Analysis on the Current Situation of Supply Chain Operation Management in D Enterprise - Gao, Shijun (International Journal of Global Economics and Management, 2025)
Taking D food manufacturing enterprise as the research object, this paper analyzes the current situation of its supply chain operation management and finds that there are problems in procurement management, such as low efficiency of internal approval and lack of strategic cooperation suppliers. In inventory management, the setting of safety stock does not consider the buffer for emergencies and does not implement differentiated management. Besides, the integration degree of the supply chain information system is low. To address these issues, optimization measures such as clarifying the time limit for procurement approval, improving the supplier assessment mechanism, and introducing advanced supply chain management software are proposed to enhance the supply chain operation efficiency of D enterprise.